2017
DOI: 10.14194/ijmbr.6.3.2
|View full text |Cite
|
Sign up to set email alerts
|

Infant carrying-related low back pain: prevalence and correlates among nursing mothers in Enugu, Nigeria

Abstract: Background: Carrying an infant is a physically demanding task which usually involves trunk loading, resulting in biomechanical stress on the musculoskeletal tissues. Aim: This cross sectional study investigated the prevalence and correlates of infant carrying-related low back pain (ICRLBP) in nursing mothers. Methods: A convenience sample of 192 Igbo-speaking mothers (18-35 years) with infants ≤ 2 years old completed a pre-tested self-administered questionnaire that included questions related to maternal demog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 17 publications
(28 reference statements)
2
7
0
Order By: Relevance
“…In this study, almost all reported using soft structured carriers and wearing baby on the front of the body. This is consistent with our hypothesis and with the prevalence of this type of carrier on the market, exposure in media (eg, celebrity babywearing moms), and advertisements to pregnant mothers, but it contrasts with the Nigerian study 13. Interestingly, most caregivers reported using more than one type of carrier and carrying with multiple positions, including wearing the baby on the back and using a wrap or ring sling carrier.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…In this study, almost all reported using soft structured carriers and wearing baby on the front of the body. This is consistent with our hypothesis and with the prevalence of this type of carrier on the market, exposure in media (eg, celebrity babywearing moms), and advertisements to pregnant mothers, but it contrasts with the Nigerian study 13. Interestingly, most caregivers reported using more than one type of carrier and carrying with multiple positions, including wearing the baby on the back and using a wrap or ring sling carrier.…”
Section: Discussionsupporting
confidence: 87%
“…About 80% of the respondents of our survey reported having experienced back pain. This is similar to the self-reported musculoskeletal complaints of mothers in the Nigerian study, with low back pain (83%) and upper back pain (75%) reported most commonly 13. Our population's ODI scores suggested that the impact of this pain on disability was minimal.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…The incidence of back injuries during child care is 34.1%, and the incidence of back pain among mothers raising infants under 4 years of age is reported to be 48% [8,9]. A total of 87.3% of baby carrier wearers complain of low back pain, regardless of the age and weight of infants using the baby carrier [10]. For example, in the case of a Korean female, the average weight of a woman in her 20s and 30s is 57.3 kg.…”
Section: Introductionmentioning
confidence: 99%